2019 IEEE 58th Conference on Decision and Control (CDC) 2019
DOI: 10.1109/cdc40024.2019.9029838
|View full text |Cite
|
Sign up to set email alerts
|

A Communication-Efficient Algorithm for Exponentially Fast Non-Bayesian Learning in Networks

Abstract: We introduce a simple time-triggered protocol to achieve communication-efficient non-Bayesian learning over a network. Specifically, we consider a scenario where a group of agents interact over a graph with the aim of discerning the true state of the world that generates their joint observation profiles. To address this problem, we propose a novel distributed learning rule wherein agents aggregate neighboring beliefs based on a min-protocol, and the inter-communication intervals grow geometrically at a rate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…First, [27] and [28] make novel connectivity assumptions, but unlike our work, neither of them allows for arbi-trarily long periods of poor (or zero) network connectivity. The same can be said about [18] and [29], even though they consider random graphs/digraphs and impose connectivity criteria only in the expectation sense.…”
Section: Introductionmentioning
confidence: 99%
“…First, [27] and [28] make novel connectivity assumptions, but unlike our work, neither of them allows for arbi-trarily long periods of poor (or zero) network connectivity. The same can be said about [18] and [29], even though they consider random graphs/digraphs and impose connectivity criteria only in the expectation sense.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the analyses of cases 1 and 2, referring to ( 13) and ( 15), and noting that γ(t) ∈ (0, 1], ∀t ∈ N, we conclude that the bound in (15) holds for each t k ∈ I such that t k > tv . Now since t k+1 − t k = g(k), for any τ ∈ N + we have:…”
Section: Proofsmentioning
confidence: 75%
“…In particular, without the event condition in Eq. 4, our communication strategy would boil down to a simple time-triggered rule, akin to the one studied in our recent work [15].…”
Section: An Event-triggered Distributed Learning Rulementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, one ripe candidate problem is that of hypothesis-testing/statistical inference where the true hypothesis belongs to a finite set of possible hypotheses. Recent results have shown that for peer-to-peer versions of this problem [88,89], one can design principled approaches to significantly reduce communication.…”
Section: Discussionmentioning
confidence: 99%